Study on the trigger mechanism and carbon behavior of catalytic reforming of wood vinegar. (26th May 2020) - Zhang, Andong; Liang, Changming; Wang, Lihong; Li, Zhihe; Yi, Weiming; Fu, Peng; Wang, Shaoqing
Abstract: Wood vinegar is a by-product with complex components in the wood carbonization process. In this paper, catalytic reforming technology was employed for reutilize of wood vinegar with a Ni/CoAl2 O4 catalyst. In order to clarify its trigger mechanism, instantaneous gases yield and components evolution were investigated at initial stage. Results showed that nearly all components in wood vinegar could efficiently participate in catalytic reforming reaction. The initiation of the catalytic reforming reaction was attributed to the cleavage of the O–H bonds caused by the adsorption of O atoms to oxygen vacancies on the surface of the catalyst. The C–H bonds could also be broken under the action of oxygen vacancies to produce hydrogen; however, the metallic carbide accompanying was the primary cause of catalyst deactivation. Graphical abstract: Image 1 Highlights: Spinel Ni/CoAl2 O4 has been introduced in the wood vinegar reforming reaction. Reaction mechanism of wood vinegar catalytic reforming has been developed. Instantaneous gas production is an effective method to analyze reaction mechanism. Carbon behavior on the surface of Ni/CoAl2 O4 has been revealed. Catalyst deactivation was primarily due to the formation of carbides in initial stage.